The Pentasulfates A2[S5O16] (A = Li, Na, Cs, Ag): Rare Species by Reactions in SO3. Issue 5 (8th February 2017) - Schindler, Lisa Verena; Struckmann, Mona; Becker, Anna; Wickleder, Mathias S.
Abstract : The reaction of various sulfate salts A2 SO4 (A = Li, Na, Ag, Cs) with neat SO3 led to the respective pentasulfates A2 [S5 O16 ] Li2 [S5 O16 ]: monoclinic, C 2/ c, Z = 4, a = 1850.71(7) pm, b = 665.45(2) pm, c = 992.80(4) pm, β = 106.764(2)°, V = 1170.72(7) × 10 6 pm 3 ; Na2 [S5 O16 ]: orthorhombic, Pbcn, Z = 4, a = 880.17(3) pm, b = 1039.88(4) pm, c = 1348.58(5) pm, V = 1234.32(8) × 10 6 pm 3 ; Ag2 [S5 O16 ]: orthorhombic, Pbcn, Z = 4, a = 884.34(4) pm, b = 1043.19(5) pm, c = 1381.83(7) pm, V = 1274.8(1) × 10 6 pm 3 ; Cs2 [S5 O16 ]: monoclinic, P 21, Z = 4, a = 892.96(3) pm, b = 859.72(3) pm, c = 978.30(4) pm, β = 101.443(2)°, V = 736.11(5) × 10 6 pm 3 . All four compounds are colorless and extremely moisture‐sensitive substances. They all contain the pentasulfate anion [S5 O16 ] 2– that has, until now, only been reported once. This comparative study of polysulfate salts with the same polysulfate anion, but varying countercations, is a crucial step in comprehending this very basic and, nevertheless, poorly investigated class of materials. Raman spectroscopy and powder diffraction complete the structural investigations. Abstract : Pentasulfates of the alkali metals can be obtained by reactions of the respective sulfates with pure SO3 . This rarely seen anion consists of five condensed [SO4 ] tetrahedra and has a very long sulfur–oxygen bond for the terminal tetrahedron.